Attenuation of NK cells facilitates mammary tumor growth in streptozotocin-induced diabetes in mice. Issue 4 (April 2018) - Gajovic, Nevena; Jurisevic, Milena; Pantic, Jelena; Radosavljevic, Gordana; Arsenijevic, Nebojsa; Lukic, Miodrag L; Jovanovic, Ivan
Abstract : Diabetic patients have higher incidence and mortality of cancer. Recent study revealed that hyperglycemia-induced oxidative stress is involved in the acceleration of tumor metastasis. We used model of high-dose streptozotocin-induced diabetes to investigate its effect on tumor growth and modulation of antitumor immune response of 4T1 murine breast cancer in BALB/c mice. Diabetes accelerated tumor appearance, growth and weight, which was associated with decreased NK cells cytotoxicity against 4T1 tumor cells in vitro . Diabetes reduced frequencies of systemic NKG2D +, perforin +, granzyme +, IFN-γ + and IL-17 + NK cells, while increased level of PD-1 expression and production of IL-10 in NK cells. Diabetes decreased percentage of NKG2D + NK cells and increased percentage of PD-1 + NK cells also in primary tumor. Diabetes increased accumulation of IL-10 + Tregs and TGF-β + myeloid-derived suppressor cells (MDSCs) in spleen and tumor. Diabetic sera in vitro significantly increased the percentage of KLRG-1 + and PD-1 + NK cells, decreased the percentage of IFN-γ + NK cells, expression of NKp46 and production of perforin, granzyme, CD107a and IL-17 per NK cell in comparison to glucose-added mouse sera and control sera. Significantly increased percentages of inducible nitric oxide synthase (iNOS) and indoleamine 2, 3-dioxygenase (IDO) producing MDSCs and dendritic cells (DC) were found in the spleens of diabetic mice prior to tumor induction. 1- methyl -DL- tryptophan, specific IDO inhibitor, almost completely restored phenotype of NK cells cultivated in diabetic sera. These findings indicate that diabetes promotes breast cancer growth at least in part through increased accumulation of immunosuppressive cells and IDO-mediated attenuation of NK cells.